A "competitive occupancy" strategy toward Co–N4 single-atom catalysts embedded in 2D TiN/rGO sheets for highly efficient and stable aromatic nitroreduction. Issue 9 (24th February 2020) - Gu, Ying; Wu, Aiping; Wang, Lei; Wang, Dongxu; Yan, Haijing; Yu, Peng; Xie, Ying; Tian, Chungui; Sun, Fanfei; Fu, Honggang
Abstract : Single-atom M–N-based catalysts have been synthesized based on the "competitive occupancy" of Ti species and Co 2+ (Ni 2+ etc. ) on GO, and can be used as a highly active and stable hydrogenation catalyst. Abstract : Single-atom catalysts (SACs) have been promising in various catalytic fields, but the controllable synthesis of SACs with high stability remains challenging. Here, we show a robust strategy toward the fabrication of highly efficient and stable SACs based on the "competitive occupancy" of two metal (M) species on graphene oxide (GO). The abundant M1 (Ti) species predominantly occupy more groups of GO, thereby leaving a tiny number of groups in the gaps of the M1 species to combine with M2 (Co 2+, etc. ) species. Consequently, this guarantees the formation of Co–N4 SACs embedded in 2D TiN/rGO sheets during nitridation. Further, TiN can act as a "spacer" to prevent Co–N4 from aggregation, thereby improving catalyst stability. Co–N4 /TiN–rGO exhibits outstanding catalytic performance for the fast conversion of highly concentrated aromatic nitro compounds (∼0.3–2 mM) into amino compounds and excellent recyclability, which is the best among reported catalysts. In contrast, TiN/rGO has no obvious activity, and Co4 N–rGO prepared without Ti competition shows poor activity and stability, which indicates the vital role of Co–N4 and TiN for obtaining the remarkable catalytic ability of Co–N4 /TiN–rGO. The reaction mechanism is also proposed based on theoretical calculations. The strategy can be used to design Ni (Fe, Cr, Cu)-based SACs.